Positive youth development programs for mental health promotion in Indian youth: an underutilized pathway - Hameed, Noufal; Mehrotra, Seema (International Journal Of Community Medicine And Public Health, 2017)
There is an unprecedented growth in the young population worldwide and especially in India and mental health of youth is an area of growing concern. The scope of convergence of the fields of positive youth development and mental health promotion among youth is becoming evident in the recent times. The paper aims to provide a brief overview of the field of PYD research in India and come up with implications for utilizing this framework for youth mental health promotion. A rapid review was carried out to examine Indian research on positive youth development and its relevance for mental health promotion through youth engagement. Two sets of key words, ‘Positive youth development’ and ‘India’ were jointly used as search words. The search was carried out in the month of April 2017, using EBSCO and ProQuest and MedIND as the electronic databases, with no restriction in the time-period of the published studies. A supplementary search of titles using Google search engine was done with eight Indian journals and one database for the period from 2010 till date. The search indicated significant paucity of Indian literature on positive youth development. A total of 24 articles were identified. Nine studies were retained of which six were non-intervention and three were intervention studies. The review suggests that PYD programs and PYD based mental health promotion programs are in a nascent stage in India with a dearth of published literature on the same. Implications for youth mental health promotion are highlighted.